EFFECT OF ZINC ELEMENT AND DEXAMETHASONE ON SOME HEMATOLOGICAL BIOCHEMICAL TESTS IN RABBITS MALE - Dheyab, D. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was conducted to investigate the effect of zinc in dose 15mg/kg.bw daily taken by the mouth and dexamethasone 4mgIkg.Bw by injection for 30days on some hematological biochemical tests and some histological changes of liver spleen in male rabbits. Thirty rabbits were used that divided into 3 randomized groups (each group contain 10 male rabbits ). Control group was taken normal food and water, Zinc group that gave zinc at dose of 15mg/kg.BW/daily/oral on 1, 2, 3, 4 weeks. Dexamethasone with zinc group : Employ dexamethasone 4mg/Kg.Bw . I.M dialy for 1 and 2 weeks for experiment and at 3, 4th weeks they gave zn 15mg/lKg.Bw day/orally. Blood samples were taken from the heart directly in 2 and 4weeks to examine packed cell volume (pcv), white blood cells (WBCs), Red blood cells (RBCs) with differential Leuckcyte count.separation blood collection to plasma and examine glucose mg/dl , cholesterol mg/dl. In histological tests, rabbits were killed and separate their organs tissue from the body to examine liver and spleen. The results revealed a decrease in level of RBCs, pcv after treatment with zinc 15, mg/Kg.Bw orally (zinc group) and increase in WBCs with differential leuckocyte count specially neutrophil cell, while biochemical tests show increase in glucose and cholesterol levels after treatment with dexamethasone 4mglkgBw. I/M seen increase in counts of RBCs , PCV, WBCs and differential lenkocyte count and decrease in glucose with cholesterol parameters, histological changes show change in liver after treatment by dexamethasone 4mglKg.Bw ,spleen tissue seen necrosis and pigmentation with hemorrhage after take dexamethasone 4mglkg in (dexamethasone + zinc group). Results also showed that zinc enhanced the immune system in at normal dose for limited time because of its effect on other mineral such as copper and causes anemia , while the dexamethasone is a drug used for antianflammatory but for a short time.